Exploratory factor analysis on Food Insecurity Experience Scale (FIES): latest food insecurity measurement tool by FAO / Nurfatiha Zulkarnain Helmi, Khairil Anuar Md. Isa and Mohamad Ghazali Masuri - Zulkarnain Helmi, Nurfatiha; Md. Isa, Khairil Anuar; Masuri, Mohamad Ghazali (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Food insecurity is a known health-related problem worldwide. Recently, the Food Agriculture Organisation (FAO) releases the latest measurement scale to gauge food insecurity experiences, namely the Food Insecurity Experience Scale (FIES), which was designed to have cross-cultural equivalence and validity. This study aimed to validate FIES's reliability when implementing it in Malaysia by using exploratory factorial analysis (EFA). FIES had been translated into Malay language by Malaysian Institute of Translation and Books (ITBM). This cross-sectional study was conducted among the community in Felda Bukit Cherakah, Puncak Alam Selangor (n=124), with the translated version of FIES. Factor analysis on the FIES questions showed that there were two underlying structures, while the Cronbach alpha coefficient indicates that FIES had acceptable internal consistency. FIES is a valid and reliable measurement tool for food insecurity situation among the Malaysian population.